Frequency diversity improvement factor for rain fade at terrestrial link in tropical region - Kesavan, U.; Islam, Md. Rafiqul; Abdullah, Khaizuran; Tharek, A.R. (IEEE, 2016)
Fade mitigation technique (FMT) is a method to overcome the rain fade effects in microwave communication link. The frequency diversity method using switching technique was used and implemented in this research. The frequency diversity improvement factor (FDIF) proposed by ITU-R was analysed using measured data. The measurement was used as a benchmark to evaluate the predicted and proposed the FDIF. New frequency diversity improvement factor (FDIF) model was developed based on rain fade data measured at 5.8, 15 and 26 GHz. The proposed model validated, measured and predicted data for the 5.8, 15 and 26 GHz which had simultaneous operation during rains was found to have close agreement.